The Suicide Phenomenon and Its Treatment in the Islamic Psycho-Spiritual Perspective - Santoso, Agus; Robaniyah, Nur; Bin Ali, Muhammad Noor (Balai Penelitian dan Pengembangan Agama Semarang, 2024)
Suicide is one of the leading causes of death. The suicide phenomenon in 2023 continues to increase both nationally and internationally. This phenomenon is directly compared to the increasing problems experienced by individuals both internally and externally. This condition needs intensive attention from the public. This study needs to be further studied by public welfare policymakers, social workers, and educators. This article was written to answer two questions. First, how do we map the triggers of suicide behaviour? Second, how does Islam’s psycho-spiritual analysis deal with the problem of suicide? The study uses a descriptive qualitative approach with literature studies supported by up-to-date data with verification and proof from various psychological, social, and religious perspectives. The study is expected to contribute to the understanding of suicide triggers, both internal and external, as well as its tactical approach to Islamic psycho-spirituality. Islamic psycho-spirituality is a treatment that involves self-integration from a psychological perspective that affects thoughts, feelings, and behaviour. The prevention of suicide behaviour from a psycho-spiritual perspective can be done with tarbiyyah ruhaniyyah and spiritual groups.